Experimental demonstration of a predictable single photon source with variable photon flux. (21st March 2017) - Vaigu, Aigar; Porrovecchio, Geiland; Chu, Xiao-Liu; Lindner, Sarah; Smid, Marek; Manninen, Albert; Becher, Christoph; Sandoghdar, Vahid; Götzinger, Stephan; Ikonen, Erkki
Abstract: We present a predictable single-photon source (SPS) based on a silicon vacancy centre in nanodiamond which is optically excited by a pulsed laser. At an excitation rate of 70   M H z the source delivers a photon flux large enough to be measured by a low optical flux detector (LOFD). The directly measured photon flux constitutes an absolute reference. By changing the repetition rate of the pulsed laser, we are able to change the photon flux of our SPS in a controllable way which in turn can act as a reference. The advantage of our method is that it does not require precise knowledge of the source efficiency, but the source is calibrated by the LOFD and can be used for detector responsivity characterizations at the few-photon level.